Predicted proteins that catalyze poly unsaturated Fatty acid synthesis in indonesian marine Diatom chaetoceros gracilis - SUHARTONO MAGGY THENAWIDJAJA; ALBERTA RIKA PRATIWI; DAHRUL SYAH; LINAWATI HARDJITO (International Journal of Pharma and Bio Sciences, 2017)
Poly Unsaturated Fatty Acid (PUFA) is valuable lipid due to their benefits for nutrition and health, and diatom is known as an excellent source of PUFA. Mechanism of PUFA synthesis in diatom is controlled by protein catalysts. The diatom was grown in the specific media; the cells were harvested and the extracellular proteins were extracted for two dimentional electrophoresis experiment. The cells were sonicated and the fatty acids content was analysed using GC/MS. The proteins involved in PUFA biosynthesis were predicted based on their molecular weight, pI and the following bioinformatic analysis. A preliminary hypothesis on PUFAs biosynthesis in Indonesian diatom Chaetoceros gracilis was suggested based on this analysis In conclusion, we suggested eleven proteins involved in the biosynthesis of PUFAs as : Δ9 DES, Δ6 DES, ELO Δ6, precursor ω-6 DES, precursor ω-3 DES, spingolipid Δ8 DES, Δ12 DES, Δ4 DES, microsomal Δ4 DES, microsomal ω-6 DES and microsomal Δ6 DES.